2013
DOI: 10.1007/s12010-013-0260-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase Partitioning as a Rapid and Easy Method for the Purification and Recovery of Catalase from Sweet Potato Tubers (Solanum tuberosum)

Abstract: Three-phase partitioning (TPP) was used to purify and recover catalase from potato crude extract. The method consists of ammonium sulfate saturation, t-butanol addition, and adjustment of pH, respectively. The best catalase recovery (262 %) and 14.1-fold purification were seen in the interfacial phase in the presence of 40 % (w/v) ammonium sulfate saturation with 1.0:1.0 crude extract/t-butanol ratio (v/v) at pH 7 in a single step. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…In this study we planned to reveal the results of only one-step TPP for purification of invertase from bitter melon. The results show that while the purification fold (10.48) is better than some previous studies Dhananjay and Mulimani, 2008;Duman and Kaya, 2013;Hussain et al, 2009;Liu et al, 2006), activity recovery (20.28%) is inadequate when only one-step TPP is used, and it may be increased by applying TPP again or other steps.…”
Section: Three-phase Partitioning Of Invertase From M Charantiamentioning
confidence: 67%
See 2 more Smart Citations
“…In this study we planned to reveal the results of only one-step TPP for purification of invertase from bitter melon. The results show that while the purification fold (10.48) is better than some previous studies Dhananjay and Mulimani, 2008;Duman and Kaya, 2013;Hussain et al, 2009;Liu et al, 2006), activity recovery (20.28%) is inadequate when only one-step TPP is used, and it may be increased by applying TPP again or other steps.…”
Section: Three-phase Partitioning Of Invertase From M Charantiamentioning
confidence: 67%
“…This may be the result of increased flexibility of the enzyme molecule at TPP conditions. A noteworthy increase in the catalytic activity and yield of some enzymes obtained from TPP was reported Duman and Kaya, 2013;Dogan and Tari, 2008; Sharma and Gupta, 2001a;Gagaoua et al, 2014Gagaoua et al, , 2016.…”
Section: Three-phase Partitioning Of Invertase From M Charantiamentioning
confidence: 92%
See 1 more Smart Citation
“…Many important biomolecules such as green fluorescent protein (GFP), xylanase, and antigenic proteins have been recovered by using this methodology [149151], demonstrating its feasibility to be integrated into a purification process. Recently, catalase was purified from sweet potato tubers in a single step using TPP with 14.1 fold purification [152]. However, recovery of organic solvent for multiple uses and validation of its successful removal from the final product are important considerations.…”
Section: Phase Partitioningmentioning
confidence: 99%
“…TPP has also been used in one step for concentration and purification of several proteins and enzymes e.g. invertase from tomato (Özer et al, 2010), glucoamylase from Aspergillus niger and pullulanase from Bacillus acidopullulyticus (Mondal, Sharma, & Gupta, 2003), proteins secreted from Corynebacterium pseudotuberculosis (Paule et al, 2004), aryl alcohol oxidase from Pleurotus ostreatus (Kumar & Rapheal, 2011), catalase from sweet potato tubers (Duman & Kaya, 2013). From these studies, it was observed in each case that an increase over 100% of enzymatic activity in the medial layer containing the precipitated enzyme could be achieved.…”
Section: Introductionmentioning
confidence: 99%